Active3D: Vector of collaboration, between sharing and data exchange - Cruz, Christophe; Nicolle, Christophe (INFOCOMP Journal of Computer Science, 2006)
This paper presents a new method to structure building information with semantic and 3D. On this method the web platform Active3D-Build was developed. The kernel of this system, composed of information management processes and information sharing processes, is based on IFC files. These files allow us to structure geometric and semantic data. Moreover, these files are used as a structure for interoperability between CAD software.